Evaluation of Dental Hygiene Practices Among Public Secondary School Students in Awka Education Zone: Focus on Brushing and Flossing Habits - Stella, Nwankwo Nonyelum (Lembaga Riset Mutiara Akbar, 2024)
This study was designed to analyzed the dental hygiene practices among public secondary school students in awka education zone of Anambra state. Four research questions were formulated to guide the study. The research design for this study is a descriptive survey. The Population of this study is made up of sixty-four (64) public secondary schools in Awka Education zone of Anambra state. The sample size is 1000 students. Instrument used for the study was a self-structured questionnaire. The instrument was validated by three experts, two in measurement and evaluation from Educational Psychology, Nwafor Orizu College of Education Nsugbe and one from Health education department. The scores of data collected were correlated using Pearson Product Moment Correlation, and it gave rise to 0.75. In analyzing the data, the researcher used weighted mean score and standard deviation in answering the research question. The study’s findings highlighted positive attitudes toward dental hygiene practices among public secondary school students. Regular brushing twice daily was seen as essential for preventing cavities, promoting fresh breath, and maintaining overall oral health. Brushing at night was particularly valued for its role in protecting enamel by removing bacteria. Students also acknowledged the benefits of flossing, noting its effectiveness in clearing debris, reducing the risk of gum disease, and alleviating toothache. However, awareness about flossing was less widespread, indicating an area where knowledge and frequency could be enhanced to further improve dental hygiene practices among students. Recommendations were made that implement awareness campaigns within schools to educate students, teachers, and parents on the importance of maintaining good oral hygiene practices. These campaigns can include workshops, seminars, and distribution of informative materials. Educational implications, conclusion and suggestions for further study were also revealed.